The Relationship Between Obesity and Allergies with Olfactory Disorders in Covid-19 Patients - Pratama, Yudistira; Kusuma Dewi, Anna Mailasari; Muyassaroh; Hariyati, Riece; Yusmawan, Willy (RSUP Dr. Kariadi, 2023)
Background: The prevalence of olfactory disorders is around 68% - 85% which occurs in COVID-19 patients with obesity and allergies as risk factors. The abnormalities olfactory pathways can cause by inflammatory response in adipose tissue in obese patients and excessive inflammation due to hyperreactivity of the immune system to allergens in allergic patients. This study aims to analyze the relationship between obesity and allergies to the occurrence of olfactory disorders in COVID-19. Method: It was an observational study during pandemic. Subjects were adult COVID-19 patients in the dr. Kariadi Hospital from June to July 2021. Patient with complete medical record ask for olfactory and allergic questionnaire. Patient with nasal tumor were excluded. Result: We found 100 subjects who meet the criteria. There was a significant difference in smell disturbances between obese and non-obese subjects. (p = 0.019, OR 4.99). There was a significant difference (p=0.001) in complaints of olfactory disorders between allergic and non-allergic subjects, whereas all allergic subjects experienced olfactory disorders. Conclusion: Obesity and allergies are corelated with impaired smell in COVID-19 patients.